Studies on fiber reinforced thermoplastic composite and their characteristics - Nagarajan Sathish (2016)
This study examined the development and characteristics of new fiber reinforced thermoplastic composites. Different materials were tried during the experiment. With these materials, single yam composites and composite laminates were fabricated. Tensile test was performed on these specimens using Instron 5569 machine. Single yam composites were fabricated with IOmm and 138mm gauge lengths and the composite laminates were fabricated with different fiber volume ratio having a gauge length of 138mm. The ultimate strength, Young’s modulus, maximum load carrying capacity and the other parameters varied with gauge length for the single yam composites. When gauge length of Elvax 3185 matrix specimen was increased from IOmm to 138mm, the maximum load reduced and tensile strength increased, but for the HDPE matrix specimen the phenomena were exactly opposite. Like single yam, the laminate’s characteristics also differed for different fiber volume ratio. When the fiber volume ratio was increased, Elvax 3185 matrix specimen’s load carrying capacity and Young’s modulus increased and the ultimate strength decreased. It was vice versa for HDPE matrix specimens. In the beginning, the laminates were fabricated and tested using only one type of resin for each laminate. After the laminates were fabricated with bi-polymer mix matrix and tested. Two resins were mixed to produce a new resin film and then using that resin film, the new laminates were fabricated and tested using Instron 5569 machine. When compared with the results of the single thermoplastic laminate, the mixed resin laminate provided better results. The uniqueness of this dissertation is its trials with thermoplastics and using them to produce distinctive glass fiber composites.